2016
DOI: 10.1016/j.virol.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on chimeric Sesbania mosaic virus coat protein: Revisiting SeMV assembly

Abstract: The capsid protein (CP) of Sesbania mosaic virus (SeMV, a T=3 plant virus) consists of a disordered N-terminal R-domain and an ordered S-domain. Removal of the R-domain results in the formation of T=1 particles. In the current study, the R-domain was replaced with unrelated polypeptides of similar lengths: the B-domain of Staphylococcus aureus SpA, and SeMV encoded polypeptides P8 and P10. The chimeric proteins contained T=3 or larger virus-like particles (VLPs) and could not be crystallized. The presence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…We use four capsids as test cases to evaluate the quality of BOSE modes. The four capsids are: capsid of Satellite Tobacco Necrosis Virus (STNV, pdb-id: 4V4M) [ 31 ], capsid of Sesbania mosaic virus (SeMV, pdb-id: 4Y5Z) [ 32 ], a mutant structure of the capsid of Grouper nervous necrosis virus (GNNV, pdb-id: 4RFT) [ 33 ], and capsid of a lumazine synthase from the thermophilic bacterium Aquifex aeolicus (AaLS, pdb-id: 5MPP) [ 34 ]. The four capsids all have icosahedral symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…We use four capsids as test cases to evaluate the quality of BOSE modes. The four capsids are: capsid of Satellite Tobacco Necrosis Virus (STNV, pdb-id: 4V4M) [ 31 ], capsid of Sesbania mosaic virus (SeMV, pdb-id: 4Y5Z) [ 32 ], a mutant structure of the capsid of Grouper nervous necrosis virus (GNNV, pdb-id: 4RFT) [ 33 ], and capsid of a lumazine synthase from the thermophilic bacterium Aquifex aeolicus (AaLS, pdb-id: 5MPP) [ 34 ]. The four capsids all have icosahedral symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…No special features such as pseudo-translation or twinning were observed in the data set. Examination of the unit-cell parameters, which were typical of a small protein crystal, suggested that the chimeric protein had not assembled into virus-like particles, as observed in other similar experiments (Gulati et al, 2016). Because the unit-cell parameters were different from those of the other crystals obtained for various constructs of the SeMV coat protein, it was speculated that a proteolytic cleavage product of the viral coat protein might have been crystallized.…”
Section: Difficulties Encountered In Determining the Crystal Structurmentioning
confidence: 74%
“…In one of the crystallization trials, a chimeric construct of the well studied Sesbania mosaic virus (SeMV; Subramanya et al, 1993;Murthy et al, 1997) in which the N-terminal 65 residues were replaced by Staphylococcus aureus protein A (SpA) (NÁ65 CP-B; Gulati et al, 2016) appeared to crystallize in space group P2 1 using the hanging-drop vapour-diffusion method. The crystallization drop consisted of 2 ml protein sample (20 mg ml À1 ) and 2 ml crystallization buffer (0.1 M bistris pH 6.5, 20% PEG MME 5000) incubated at 22 C. Crystals were obtained in about two weeks.…”
Section: Difficulties Encountered In Determining the Crystal Structurmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant plasmid (pRSETC CP sdm) was digested with AfeI enzyme. B domain gene, PCR amplified using pRSETC NΔ65B CP 45 as template and B domain specific primers ( Table 1 ), was ligated to AfeI digested pRSETC CP sdm to form pRSETC SLB His. For removal of the N terminal Histidine tag, the entire construct was PCR amplified using CP specific primers ( Table 1 ) digested with EcoRI and inserted in NdeI end filled and EcoRI cut pRSETC vector.…”
Section: Methodsmentioning
confidence: 99%